2023
DOI: 10.1097/md.0000000000033337
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary artery tumors easily misdiagnosed as pulmonary embolism: A review

Abstract: Primary pulmonary artery tumors (PPATs), originating from the pulmonary artery intima, are rare tumors characterized by pulmonary artery luminal occlusion and pulmonary hypertension. Diagnosis of this rare entity is a challenging dilemma with the need for a high expertise in the radiological and pathological identification of PPATs. computed tomographic pulmonary angiography of PPATs may show filling defects, which are easily misdiagnosed. The radionuclide scan, along with other imaging examinations, can assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…On MRI, tumor embolism demonstrates increased gadolinium enhancement when compared to bland emboli. On 18 F-FDG PET/CT tumor thrombus will demonstrate increased FDG uptake with the additional advantage that it can help identify a distant primary source and other sites of metastatic disease [ 1 , 2 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On MRI, tumor embolism demonstrates increased gadolinium enhancement when compared to bland emboli. On 18 F-FDG PET/CT tumor thrombus will demonstrate increased FDG uptake with the additional advantage that it can help identify a distant primary source and other sites of metastatic disease [ 1 , 2 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT-guided transthoracic biopsy is one option, however given the location it poses the high risk of bleeding. Endobronchial ultrasound and transbronchial needle aspiration (EBUS-TBNA) is another option which allows better visualization of the tumor and blood flow via doppler ultrasonography, however due to increased pulmonary artery pressure and resultant bronchial artery hypertrophy, there is also a high risk of bleeding [ 2 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of preoperative biopsy in PAS patients remains controversial. Some studies have reported successful pathological diagnosis through CT scan-guided transthoracic aspiration, EBUS-TBNA, and ECGF biopsy ( 23 ). Among these seven patients, two using EBUS-TBNA and three of five using ECGF were confirmed to have malignancy.…”
Section: Discussionmentioning
confidence: 99%